Lethal treasure [large type] - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries, 2013)
For Josie Prescott, an abandoned storage unit is the perfect place to find some killer treasure. In the auction crowd is local interior designer Henri Dubois, bidding against a stranger. Josie is thrilled to win a small unit filled with Depression-era glassware and stunning vintage jewelry. Henri's unit includes hand-painted silent movie posters, which he asks Josie to appraise. But the next morning, she receives a frantic call from Henri's wife: he never made it home.